32.4k views
15 votes
Hello people ~
Sketch the graph for y=cot ^-1 (cot x)


User Todd White
by
5.1k points

1 Answer

8 votes

Answer:


\sf y=cot^(-1)(cot(x))


\sf \implies cot(y)=cot(x)


\sf \implies (1)/(tan(y))=(1)/(tan(x))


\sf \implies tan(x)=tan(y)


\sf \implies y=x


\sf \implies y=x\pm\pi n

Hello people ~ Sketch the graph for y=cot ^-1 (cot x) ​-example-1
User Ranojan
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.